We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
135
1
avatar+569 

pls help me with this thx

 Mar 12, 2019
 #1
avatar+102355 
+1

When x = -2,   then function A  = f(-2)  =  3 - (-2)^2 =  3 - 4  =  -1

 

When x = -2, function B = g(-2)  =  -1

 

So

 

f (-2) = g(-2)   =  -1       (second answer )

 

 

cool coolcool

 Mar 12, 2019

12 Online Users